«RECRUITMENT» AND PEASANTS GENERAL ETAPUVANNYA DISTRICTS «DNEPROPETROVSK» TO WORK IN GERMANY - Gandabyra, N. Ya. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
The paper was made a brief analysis of recent research and publications modern Ukrainian scientists. In the article the author tried to explore the politics of the German occupation authorities general constituencies «Dnepropetrovsk» on the export of local villagers for forced labor in Germany. The reason that prompted the occupation authorities most of the local population, particularly the peasants as cheap labor on the territory of the Reich. The attention was to the role of the occupation of the press during this recruit, which is depicted only good conditions of life and work «Ostarbeiters» in exile. It was shown involvement of local authorities and information tools and the use of various methods of influence (promotion and intimidation) during recruit manpower to work in the Third Reich, exhaustion thus village and the undermining of its gene pool. It was regarded the role of district chiefs and village councils and local police districts general «Dnepropetrovsk» in this recruiting campaign using them during recruit and threats of violent reprisals. But despite this, often there have been cases of sabotage «recruited». It was analyzed archival documents, letters and memories «Ostarbeiters». Particular attention is paid to the conditions recruit pursued by the occupiers, transportation and future life and work «Ostarbeiters» Dnieper arrival of the Third Reich, the use of workers «recruited» in enterprises, agriculture and other serious works.